Pengaruh Brand Love dan Kepercayaan Merek terhadap Loyalitas Merek (Pada Konsumen Eiger di Pandaan Pasuruan) - Mokhammad Fakhrur Rozi (CV. Satria Jaya, 2023)
The aim of this research is to analyze and determine the influence of brand love and brand trust on brand loyalty. The type of research used is multiple linear regression assisted by processing using the SPSS (statistical package for social sciences) version 22 program so that primary data is obtained. The population in this study were consumers at the EIGER Pandan Store. The sampling technique was carried out using a census and the researcher used a questionnaire to collect data. There are two independent variables in this research, namely brand love and brand trust. Meanwhile, the dependent variable in this research is brand loyalty. The results of this research state that brand love and brand trust simultaneously have a positive and significant effect on brand loyalty received. This can be proven by the results of the F test with a sig value. 0.00 is smaller than the standard significance of 0.05 which indicates significant results. Consumer perception, diversity and brand image have a significant influence on consumer buying interest